Type I ROP16 regulates retinal inflammatory responses during ocular toxoplasmosis (2019)
Ocular toxoplasmosis (OT), mostly retinochorioditis, is a major feature of infection with the protozoan parasite Toxoplasma gondii. The pathophysiology of this infection is still largely elusive; especially mouse models are not yet well developed. In contrast, numerous in vitro studies showed the highly Toxoplasma strain dependent nature of the host-parasite interactions. Some distinct polymorphic virulence factors were characterized, notably the rhoptry protein ROP16. Here, we studied the strain-dependent pathophysiology in our OT mouse model. Besides of two wild type strains of the canonical I (RH, virulent) and II (PRU, avirulent) types, we used genetically engineered parasites, RH?ROP16 and PRU ROP16-I, expressing the type I allele of this virulence factor. We analyzed retinal integrity, parasite proliferation and retinal expression of cytokines. PRU parasites behaved much more virulently in the presence of a type I ROP16. In contrast, knockout of ROP16 in the RH strain led to a decrease of intraocular proliferation, but no difference in retinal pathology. Cytokine quantification in aqueous humor showed strong production of Th1 and inflammatory markers following infection with the two strains containing the ROP16-I allele. In strong contrast, immunofluorescence images showed that actual expression of most cytokines in retinal cells is rapidly suppressed by type I strain infection, with or without the involvement of its homologous ROP16 allele. This demonstrates the particular immune privileged situation of the retina, which is also revealed by the fact that parasite proliferation is nearly exclusively observed outside the retina. In summary, we further developed a promising OT mouse model and demonstrated the specific pathology in retinal tissues. © 2019 Rochet et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.